Okostnjaki v omari ZVO-1 - Sekirnik, Janez (Podjetje in delo, 2024)
The implementation of the Environmental Protection Act (ZVO-2), in the part concerning waste management and the fulfilment of producers’ obligations through Producer Responsibility Organisations (PROs), has been suspended due to a petition for a review of its constitutionality. Consequently, Article 20 of the Environmental Protection Act (ZVO-1) and the regulations adopted thereunder continue to apply to the joint fulfilment of producer waste management obligations. The system of joint fulfilment of producer waste management obligations under the ZVO-1 has a number of shortcomings, one of which is the financial compensation mechanism as regulated by the Regulation on waste electric and electronic equipment and the Regulation on waste grave candles. In practice, the relatively clear provisions of these two regulations cause enormous difficulties for the PROs, for the competent ministry and, according to a recent decision, also for the courts. The financial compensation mechanism should ensure that each PRO bears the share of the waste management costs for which its affiliated producers are responsible, even if this waste was actually collected and treated by another PRO. The financial compensation mechanism allows a PRO with excess collected waste to make or claim a financial compensation from a PRO that has not reached the relevant quantities. In practice, the financial compensation mechanism does not work, which gives rise to a number of proceedings in the courts and before the competent ministry and inspectorate. The author argues that the difficulties in implementing financial compensation stem from the passive approach of the competent ministry and inspectorate and the misinterpretation of their positions. The author outlines the main arguing points between the stakeholders involved and offers arguments for a solution to the resulting impasse.
Keywords: Environmental Protection Act; financial compensations; finančne izravnave; joint fulfilment of producer waste management obligations; nosilci skupnih načrtov; obveznosti proizvajalcev; producer obligations; Producer Responsibility Organisations; ravnanje z odpadki; skupno izpolnjevanje obveznosti; waste management; Zakon o varstvu okolja